(untitled) (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: We report a case of a 3-year-old boy who presented with left eye swelling, low-grade fever, pallor, and generalized lymphadenopathy. He was diagnosed with a case of B-cell acute lymphoblastic leukemia (ALL) on the basis of morphology and immunophenotyping of bone marrow. Orbital manifestation is rarely seen in ALL; rather it is more common in acute myeloid leukemia (AML). Knowledge regarding the unusual presentation of ALL will help timely diagnosis and treatment which is crucial for preserving the eye as well as the vision. Ibrahim Card Med J 2022; 12 (2): 64-66